2009
DOI: 10.1158/0008-5472.can-08-2246
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activity of the Src Family Kinase Inhibitor Dasatinib and Oxaliplatin in Colon Carcinoma Cells Is Mediated by Oxidative Stress

Abstract: Chemotherapeutic regimens for the treatment of colorectal cancer generally include oxaliplatin, although inherent and acquired resistance is common. One potential mediator of oxaliplatin sensitivity is the nonreceptor protein tyrosine kinase, Src, the activity of which correlates with disease stage and patient survival. Therefore, we investigated the effects of Src inhibition using the tyrosine kinase inhibitor dasatinib on oxaliplatin sensitivity. We show that oxaliplatin acutely activates Src and that combin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
135
2
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(148 citation statements)
references
References 43 publications
5
135
2
6
Order By: Relevance
“…One study found that Src activity mediates oxaliplatin (platinum-based chemotherapeutic agent) sensitivity and resistance, and reduced expression of Src leads to increased cytotoxicity in response to oxaliplatin (40). Therefore, sensitivity to cisplatin and other platinum-based chemotherapeutic agents might also be affected by altered Src expression or activity in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that Src activity mediates oxaliplatin (platinum-based chemotherapeutic agent) sensitivity and resistance, and reduced expression of Src leads to increased cytotoxicity in response to oxaliplatin (40). Therefore, sensitivity to cisplatin and other platinum-based chemotherapeutic agents might also be affected by altered Src expression or activity in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…Dasatinib is well tolerated and the drug has entered the clinic for patients with leukemia (Kantarjian et al, 2007). Dasatinib has shown activity against colon cancer cells in preclinical models (Serrels et al, 2006;Kopetz et al, 2009). The potential of dasatinib in adenomas has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Src kinase is a non-receptor tyrosine kinase which is a convergence point for numerous oncogenic pathways [133] and has been implicated in mechanisms of oxaliplatin resistance in colorectal cancer [134]. In preclinical mEOC models, encouraging results have been achieved by targeting Src signaling with dasatinib [135] and KX-01; a novel Src inhibitor and antitubule agent, in synergy with oxaliplatin [136].…”
Section: Targeting Src and Pi3k/akt Pathwaysmentioning
confidence: 99%